Application of the TOPSIS method in determining the location of a new gret laundry branch / Muhammad Syahrizal … [et al.] - Syahrizal, Muhammad; Mesran, Mesran; Kristin Purba, Rohan; Utomo, Dito Putro (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
In opening a new branch, one important factor that needs to be considered is the selection of a new branch location. Because the location of a new branch determines the future journey of a business. If the selection of the location of the business is carried out carefully, then the business that is run will run well and vice versa. In determining the location of a new branch will be very difficult if done manually. Therefore, we need a system that can help solve these problems, SPK is a computer-based system that will ultimately help in deciding where to find a good new branch location. In using SPK, a method is needed. The method used in this study is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. TOPSIS is a method in SPK which means it is a ranking method that uses the longest and shortest distances to measure its ranking.